A Review on The Production of Fermented Beverage as a Post-Harvest Processing Alternative For Mango, Banana and Purple Sweet Potato - Sonia Yurista; Pingkan Aditiawati (School of Life Sciences and Technology, Institut Teknologi Bandung, 2021)
West Java is one of the regions in Indonesia that produces large numbers of mango, banana, and purple sweet potato. After harvesting, these commodities will undergo physical, chemical, and physiological changes so that further post-harvest processing is needed. One of the post-harvest processing that can be done is fermentation. Fermenting mango, banana, and purple sweet potato into wine is a simple and efficient method that can increase the economic value of the product. Wine is an alcoholic beverage made from grapes; however, any fruit and tuber could be used for wine-making. The article reviews the potential of mango, banana, and purple sweet potato for wine production, the microbes involved, and pretreatments of mango, banana, and purple sweet potato.